PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DI KANTOR TANAH GROGOT KELURAHAN KABUPATEN PASER - Gufron Athari; Achmad Aprianur Firdaus; Ismail (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
The purpose of this study was to determine the effect of motivation (Physiological needs, security needs, social needs, esteem needs and self-actualization needs) on employee performance at the Tanah Grogot Village Office, Paser Regency. And which variable among the motivational variables has the dominant influence on employee performance. The benefit to be achieved in this research is that it can be used to improve performance in the future. From the results of the validity test, it can be seen that each item 1 to 16 has rcount valid, with a rcount of 0.3338 rcount>rtable, so each item is valid. Meanwhile, the results of the Cronbach's reliability test were negligent, namely 0.847 > 0.6, so all statement items can be stated as reliable. From the multiple linear regression analysis method, we get the function equation Y = 0.943+0.502X1+0.035X2+0.096X3+0.098X4+0.194X5. From the calculation of the coefficient of determination (R2) of 0.661 or 66.1%, the value of the coefficient of determination shows the large contribution of the independent variable (motivation) to the dependent variable (employee performance), while the remaining 33.9% is explained by other factors. Based on the partial test (T test) it is known that the motivation variable (X) obtained the largest tcount value of 4.575 while the ttable value is 1.69913, it can be seen that tcount> ttable or 4.575> 1.69913 this is also evidenced by a significant value of 0.000 so it can be concluded that the motivational variable (X) has a significant effect on employee performance (Y) at the Paser District Office, Tanah Grogot, Paser District.